Synthesis and Activity Test of 1-Allyl-3-(4-tertiary-Butylbenzoyl) Thioureaas a Candidate of an Analgesic Drug - Rais Razak; Siswandono Siswandono; Juni Ekowati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Urea derivatives showed good analgesic activity compared to diclofenac sodium.  The addition of the allyl group to the thiourea and 4-tertiary-butylbenzoyl chlorideis expected to provide a better analgesic effect. Objective: The research aimed to synthesize 1-allyl-3-(4-tertiary-Butylbenzoyl) Thiourea and determine its analgesic activity in mice (Mus musculus). Methods: The synthesis was carried out by a modified Schotten-Baumann reaction, via nucleophilic substitution reaction of allylthiourea on 4-tertiary-butylbenzoyl chloride.  A writhing test was performed to observe analgesic activity in the test compound.  Confirmation of the structure of pure 1-allyl-3-(4-tertiary-Butylbenzoyl) Thiourea was obtained through UV, IR, 1H-NMR, and 13C-NMR data. Results: The compound showed better pain inhibition activity compared to diclofenac sodium, with ED5019,018 mg/kg BW. Conclusion: The compound 1-allyl-3-(4-tertiary-butylbenzoyl) thiourea showed better analgesic activity than diclofenac sodium.